Optimization of Helium Inflating on Heat Dissipation and Luminescence Properties of the A60 LED Filament Lamps - Huang, Guangyao; Li, Yuanxing; Zhao, Lite; Zeng, Qingguang; Chen, Yizhan; Li, Bingqian (International Journal of Photoenergy, 2019)
LED filament lamp has the characteristics of nearly 360° lighting angle, high brightness, and low energy consumption, turning it gradually into the best substitute for traditional incandescent lamps. At present, due to the limitations of heat dissipation, the development of high-power LED filament lamp is restricted. Helium is a rare gas with small density and high heat transfer coefficient. It can be used as a cooling and protective gas for LED filament lamp. In this paper, we investigated the effects of helium on the heat dissipation and luminescence performance of the A60 LED filament lamps by detecting the changes of junction temperature, color temperature, and luminous flux of different ratios helium inflating in the different power A60 LED filament lamps. Through the experiment, we found the most cost-effective ratio of helium gas in the A60 LED filament lamps without improving the lamp size and the filament diameter.